STRATEGI PENGELOLAAN SUMBERDAYA PESISIR DAN LAUT BERBASIS KEARIFAN LOKAL DI KOTA ADMINISTRATIF ATAURO KOTA MADYA DILI TIMOR-LESTE - Mesquita, Domingos; Suarna, I Wayan; Windia, Wayan (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2016)
Coastal and marine resources today are degraded as a result of destructive use and short-term interests. People in the Town of Atauro have their own indigenous traditions of ancestors that are applied in the customary law, known by the locals as Tara Bandu (prohibitions). The objectives of this research are: 1) to find out the potential of coastal and marine resources as well as the extent of their utilization , 2) to determine the values of local wisdom of the coastal communities that have a relationship with the management of coastal and marine resources, 3) to determine the attitudes and behavior of the people as well as components related to management of coastal and marine resources, 4) to obtain management strategies of coastal and marine resources that is based on the local wisdom in the Town of Atauro. This study is a survey research using qualitative descriptive approach combined with SWOT analysis. Data were collected by field observations, interviews, and documentation. While the methods and techniques of data analysis used were qualitative descriptive analysis and SWOT analysis. The research results showed that the values of local wisdom that have a role in the management of coastal and marine resources are the tradition to install traps ( bubur ), local wisdom of Tara Bandu (prohibition), local wisdom in the Kampung Maquer to prohibit the capture of some types of slow-moving marine life, tradition of baku tasi and baku lai , the tradition of worshipping wooden statues and the Saint Peter’s festival. In the Village of Biqueli, there is a tradition of the prohibitions on smoking, chewing betel nut, and drinking alcoholic beverages in public places. SWOT analysis concluded that the management of coastal and marine resources in the Administrative Town of Atauro is in quadrant / conservative position, i.e. the position of improvement strategies. The strategies used in the management of coastal and marine resources are, a) preparing the regional spatial layout plan (RTRW) with the concept of one island management strategy so that the development programs do not have a negative impact on coastal and marine resources, b) preparing for annual action plans and allocating funds for the provision of facilities and infrastructure, c) human resource development through formal education, training profession, and comparative studies in the more developed areas, d) conducting a study of environmental impacts of coastal development, e) tradition to install traps and lubuk larangan /customary prohibition needs to be done to maintain the harmony of human relationships with the environment, f) giving education and extension programs for public awareness about the conservation of coastal and marine resources.
Keywords: The Atauro Island, management strategies, coastal and marine resources, local wisdom